An environmental scan of shared access to patient portals. (25th August 2017) - Wolff, Jennifer L; Kim, Victoria S; Mintz, Suzanne; Stametz, Rebecca; Griffin, Joan M
Abstract: We sought to understand the comprehensiveness of consumer-oriented information describing the availability of shared access to adult patient portals from publicly reported information on institutional websites of 20 large and geographically diverse health systems. All 20 health systems reported that they offer patients the ability to share access to their patient portal account with a family member or friend; however, the comprehensiveness of information regarding registration procedures, features, and terminology varied widely. Half of the systems ( n = 10) reported having shared access available on their patient portal registration webpage. Few systems ( n = 2) reported affording patients the ability to differentiate specific role-based privileges. No systems reported uptake of shared access among adult patients, which was variably described as "proxy, " "caregiver, " "parental, " or "delegate" access. Findings suggest that engaging families through health information technology will require greater efforts to promote awareness and differentiate privileges that respect patients' choice and control in information-sharing preferences.